The use of lesson study to support grade 2 teachers in implementing differentiated instruction to develop learners' reading comprehension skills - Shipanga, Elizabeth Magano (Rhodes University, Faculty of Education, Department of Education)
Research has found that learners in Namibia have poor reading comprehension (UNESCO, 2017). The Ministry of Education Arts and Culture (MoEAC) is concerned that teachers do not have the required pedagogical content knowledge to teach reading, and particularly reading comprehension in English Second Language. In addition, the MoEAC (2015) advocates for Differentiated Instruction (DI) to accommodate the needs of all learners in the classroom. Despite, numerous Continuous Professional Development programs, there has not been much change in the way teachers teach reading. The Lesson Study (LS) approach is viewed as a means to support teachers' professional development. It provides teachers with the agency to take responsibility for their own professional development. It is against this background that an interpretivist action research was utilised to ascertain how LS can be used to support Grade 2 teachers in implementing DI to develop learners' reading comprehension skill. This study asked the question: How can Lesson Study be used to support Grade 2 teachers in implementing Differentiated Instruction to develop the learners' reading comprehension? Data was generated through observations, document analysis and interviews. The Theory of Practice Architectures was used to analyse data. As teachers we began this study with knowledge of the goals and terminology of DI but lacked the competence to implement it. The LS process used in the study enhanced teamwork as we planned, taught, observed each other, and reflected on the lessons taught during the intervention. We shared diverse insights in a supportive environment. Despite still novices with LS and DI we worked on redesigning lessons to become more intentional in catering for the needs of all learners in developing their reading comprehension in English Second Language. The emerging evidence from this and other studies is that LS is a very useful vehicle for Continuous Professional Development (CPD), but it is time consuming and in this study planning and reflecting on the lessons had to occur after hours.
Keywords: Reading comprehension-- Study and teaching (Elementary)-- Namibia; Lesson study; Differentiated instruction; Teaching Social aspects-- Namibia